Japanese Loanwords for Clothing in Current Spanish - Fernández Mata, Rafael (2020)
Japanese loanwords related to clothing constitute the seventh biggest semantic field –position that they also share with the Japanese loanwords related to dwelling-furniture and religion-philosophy– (4 words out of a total of 92) of all such words used currently in Spanish. For the first time concerning Spanish, the clothing Japanese loanwords are described thoroughly from a formal, semantic and historical perspective in the present article. Further, the degree of adaptation of these loanwords within the Spanish lexical inventory will be indicated.